Older Adults Exhibit Greater Visual Cortex Inhibition and Reduced Visual Cortex Plasticity Compared to Younger Adults - Abuleil, Dania; McCulloch, Daphne L.; Thompson, Benjamin (Frontiers in Neuroscience, 2019)
Recent evidence indicates that inhibition within the visual cortex is greater in older than young adults. Increased inhibition has been associated with reduced visual cortex plasticity in animal models. We investigated whether the age-related increase in human visual cortex inhibition influences visual cortex plasticity. Visual cortex inhibition was measured psychophysically using binocular rivalry alternation rates (AR) for dichoptic gratings. Slower ARs are associated with a greater concentration of the inhibitory neurotransmitter GABA within the human visual cortex. Visual cortex plasticity was measured using an established paradigm for induction of long-term potentiation (LTP) -like increases in visually evoked potential (VEP) amplitude. Following rapid visual stimulation, increases in VEP amplitude are associated with greater visual cortex plasticity. The study involved two groups; young (18-40 years, n=29) and older adults (60-80 years, n=18). VEPs were recorded for a 1Hz onset/offset checkerboard stimulus before and after 9Hz visual stimulation with the same stimulus. ARs were slower in older than young adults. In contrast to most previous studies, VEP amplitudes were significantly reduced following the rapid visual stimulation for young adults; older adult VEP amplitudes were unaffected. Our AR results replicate previous observations of increased visual cortex inhibition in the older adults. Rapid visual stimulation significantly altered VEP amplitude in young adults, albeit in the opposite direction than predicted. VEP amplitudes did not change in old adults suggesting an association between increased inhibition and reduced plasticity within the human visual cortex.